Analysis of structural crashworthiness of double-hull ships in collision and grounding. (March 2021) - Liu, Bin; Villavicencio, R.; Pedersen, P. Terndrup; Guedes Soares, C.
Abstract: A conceptual design framework for collision and grounding analysis is proposed to evaluate the crashworthiness of double-hull structures. This work attempts to simplify the input parameters needed for the analysis, which can be considered as a step towards a design-oriented procedure against collision and grounding. Four typical collision and grounding scenarios are considered: (1) side structure struck by a bulbous bow, (2) side structure struck by a straight bow, (3) bottom raking, (4) bottom stranding. The analyses of these scenarios are based on statistical data of striking ship dimensions, velocities, collision angles and locations, as well as seabed shapes and sizes, grounding depth and location. The evaluation of the damage extent considers the 50- and 90-percentile values from the statistics of collision and grounding accidents. The external dynamics and internal mechanics are combined to analyse systematically the ship structural damage and energy absorption under accidental loadings. Highlights: A practical methodology for collision and grounding is proposed to evaluate the crashworthiness of double-hull structures. The crashworthy assessment is performed for four typical collision and grounding scenarios. The 50- and 90-percentile values from statistical collision and grounding accidents are considered. The external dynamics and internal mechanics are combined to analyse the ship structural damage.